Silicon carbon material, preparation method thereof and lithium ion battery

By vapor deposition on a porous carbon-loaded silicon matrix, carbon nanotubes and carbon coating are grown in situ, the problem of poor pressure resistance performance of silicon carbon materials under high compaction density is solved, and the performance of lithium-ion batteries is significantly improved.

CN119695111APending Publication Date: 2025-03-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862985.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicon carbon materials have poor voltage resistance under high compaction density, and there are expansion problems in lithium-ion batteries, which affect the rate performance and cycling performance of the battery.

Method used

By vapor deposition on a porous carbon-supported silicon matrix, metal oxides are formed, and carbon nanotubes and carbon coating are then grown in situ to form a silicon carbon material with excellent pressure resistance.

Benefits of technology

It significantly improves the voltage resistance and conductivity of silicon-carbon materials, alleviates the expansion problem of lithium-ion batteries, and comprehensively optimizes the first-effect, rate performance and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695111A_ABST
    Figure CN119695111A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbon material, a preparation method thereof and a lithium ion battery. The preparation method of the silicon-carbon material comprises the following steps: S1, carrying out first vapor deposition on a porous carbon-loaded silicon substrate to obtain a first precursor; wherein first deposition gas adopted by the first vapor deposition comprises metal salt gas; s2, performing second vapor deposition on the first precursor to obtain a silicon carbon material; wherein a second deposition gas adopted by the second vapor deposition comprises a carbon source gas. According to the preparation method, the carbon nanotubes can grow in the porous carbon-loaded silicon substrate in situ, the carbon nanotubes are dispersed more uniformly, and the obtained silicon-carbon material has excellent compaction density, pressure resistance and the like, and can effectively relieve expansion and comprehensively optimize the first effect, rate capability, cycle performance and the like after being used for a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] In existing lithium-ion batteries, the gram capacity of positive electrode materials increases slowly and has high impedance. The actual amount of lithium inserted is severely limited by the voltage of the lithium-ion battery. Moreover, under high voltage conditions, the oxygen in the positive electrode material is more likely to be released. Among the existing electrolytes, carbonate electrolytes have the advantages of high dielectric constant and high boiling point, and are difficult to be replaced by other mainstream solvents and additives in a short period of time. However, carbonate electrolytes have the disadvantage of a small voltage window. Therefore, in order to increase the capacity of lithium-ion batteries, negative electrode materials have become the mainstream improvement direction.

[0003] Silicon-carbon materials are one of the hottest areas in the new energy industry. Silicon-carbon anodes have a very high gram capacity of 1900mAh (0.8v) and a high lithium insertion potential of 0.4V (Li\Li + ), and can also inhibit lithium crystallization and is widely used; although the overall discharge platform will be reduced by about 0.1V, due to its extremely high gram capacity, a small amount of doping can increase the gram capacity of traditional negative electrode materials, and it has attracted much attention in the new energy industry.

[0004] The data show that the theoretical capacity of 5% SiC anode can reach 372 mAh g -1 The graphite anode achieves 420mAh g -1 8% silicon-carbon doping can achieve 450 mAh g -1 10% silicon-carbon doping can achieve 480 mAh g -1 In addition, due to the high density of silicon, its compaction density is much greater than that of graphite under the same pressure, making the lithium-ion battery containing it reach 800WhL -1 The volume energy density is only 500WhL -1 Compared with lithium-ion batteries containing graphite negative electrodes, there is a huge improvement. For lithium-ion batteries of the same volume or mass, even if the lithium-ion battery with silicon-carbon negative electrode material fails (defined as 80% SOC), its capacity value is still close to 600WhL -1 , which is still greater than graphite. It can be said that lithium-ion batteries containing silicon negative electrodes have many advantages over traditional lithium-ion batteries containing graphite negative electrodes in terms of energy density and cycle performance.

[0005] At present, amorphous silicon carbon prepared by silane precipitation has a higher initial efficiency and has outstanding advantages over nano silicon prepared by grinding. It is the most popular direction in the energy 3C field of the industry. The negative electrode silicon carbon technology of amorphous nano silicon-subnano silicon precipitated by silane is undoubtedly the key to leveraging the volume energy density of lithium-ion batteries to reach 1000WhL. -1 As a powerful lever, the emergence of silicon-carbon negative electrode materials has also enabled the energy density of the overall lithium-ion battery industry to increase from 3% per year to 5% per year.

[0006] However, in actual use, there are often many contradictory problems. For example, in the process of improving the volume energy density of lithium-ion batteries, it is often necessary to use silicon-carbon negative electrode materials with high compaction density. The compaction density of the negative electrode sheet usually needs to reach 1.70g·cm -3 However, at such a high compaction density, the silicon-carbon negative electrode material obtained by porous carbon deposition with high pore volume is often not pressure-resistant, but has a better effect in alleviating expansion. At the same time, the silicon-carbon negative electrode material obtained by porous carbon deposition with low pore volume is relatively pressure-resistant, but has poor expansion relief and rate performance. The main reason is that in the process of limiting expansion, lithium atoms will be embedded in the interior of the porous carbon nanoparticles, and the ion diffusion resistance will also increase invisibly. Therefore, for the current situation, the silicon-carbon negative electrode with a higher pore volume adopts a multi-layer coating process, combined with negative electrode laser drilling technology, which can barely meet the requirements of low compaction density pole pieces, but for negative electrode materials with high compaction density, high volume capacity, and high silicon-carbon material requirements, it is still far from enough.

[0007] It has been proven that the technology of coating the surface of silicon-carbon materials with carbon nanotubes can improve the rate performance of silicon-carbon negative electrodes, regardless of low temperature, room temperature or high temperature. However, in the existing coating technology, the initial efficiency and rate performance of lithium-ion batteries obtained after traditional coating of carbon tubes are still relatively poor, and the location of the carbon tubes is limited. They can only exist in the outer layer of the silicon-carbon material. They have poor dispersion and are easy to agglomerate. In addition, the aspect ratio is relatively large, and the carbon tubes are very easy to entangle and difficult to wrap into the inner layer. The method of doping carbon tubes in carbon material precursors will affect the subsequent carbonization and activation, and thus affect the overall performance of the obtained lithium-ion battery. In addition, because the carbon tubes need to be purchased from outside, it is not conducive to reducing costs and is difficult to meet large-scale mass production requirements. Summary of the invention

[0008] In order to overcome the above defects of existing silicon-carbon materials, the present invention provides a silicon-carbon material and a preparation method thereof, and a lithium-ion battery. The preparation method can grow carbon nanotubes in situ, and the carbon nanotubes are more evenly dispersed. The obtained silicon-carbon material has excellent pressure resistance, etc. After being used in lithium-ion batteries, it can effectively alleviate expansion and comprehensively optimize its first efficiency, rate performance and cycle performance.

[0009] The present invention provides a method for preparing a silicon-carbon material, and the method for preparing the silicon-carbon material comprises the following steps:

[0010] S1, performing a first vapor deposition on a porous carbon-supported silicon substrate to obtain a first precursor;

[0011] Wherein, the first deposition gas used in the first vapor deposition comprises a metal salt gas;

[0012] S2, performing a second vapor deposition on the first precursor to obtain the silicon-carbon material;

[0013] Wherein, the second deposition gas used in the second vapor deposition comprises a carbon source gas.

[0014] In the present invention, in step S1, the metal salt gas can be a soluble salt gas of a transition metal that is conventional in the art and can catalyze the growth of carbon nanotubes in the form of oxides or simple substances. The metal salt gas will be cracked simultaneously during the vapor deposition process, and the entire process will preferentially generate nano-metal oxides in the mesopores and macropores of the porous carbon-supported silicon matrix, and then generate nano-metal oxides on the surface; when the vapor deposition in step S2 is subsequently performed, carbon nanotubes will be grown in situ in the form of top growth or bottom growth, and carbon coating will be performed simultaneously. Carbon nanotubes grown based on metal element catalysis are metallic carbon nanotubes, which have the ability to conduct electrons and ions equivalent to graphene, which cannot be replaced by other carbon nanotubes.

[0015] In some embodiments, in step S1, the metal salt gas includes one or more of metal nitrate gas, metal hydrochloride gas, metal sulfate gas, metal acetate gas and metal citrate gas, preferably metal nitrate gas.

[0016] In some embodiments, in step S1, the metal salt gas includes one or more of iron salt gas, nickel salt gas, molybdenum salt gas, and cobalt salt gas.

[0017] In some preferred embodiments, in step S1, the metal salt gas includes iron salt gas, preferably iron nitrate gas. Studies have shown that when iron salt gas is used, the oxide deposited has a better catalytic carbon nanotube growth rate; among them, iron nitrate has a lower sublimation temperature, is easy to decompose and easy to control, and its decomposition product is ferric oxide, which has a strong affinity with carbon materials due to the presence of oxygen-containing functional groups. After reduction, it is easier to grow in situ with it as a substrate when growing carbon nanotubes.

[0018] In some embodiments, in step S1, the metal salt gas is obtained by sublimating the metal salt by heating it.

[0019] The absolute pressure P1 of the heating treatment is preferably 30-60 kPa, such as 50 kPa.

[0020] The temperature T1 of the heating treatment is preferably 80-550°C, such as 150°C.

[0021] In some embodiments, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at an absolute pressure P2 of 25-55 kPa, for example, 40 kPa.

[0022] In some embodiments, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at a temperature T2 of 80-550°C, for example, 150°C.

[0023] In some embodiments, in step S1, the flow rate of the first deposition gas is 3-80 mL·kg -1 ·min -1 , preferably 10-60mL·kg -1 ·min -1 , more preferably 40 mL·kg -1 ·min -1 The unit of the flow rate means the volume of the first deposition gas introduced per minute relative to per kilogram of the material in the current step.

[0024] In some embodiments, in step S1, the absolute pressure P3 of the first vapor deposition is 20-50 kPa, for example, 30 kPa.

[0025] In some embodiments, in step S1, the temperature T3 of the first vapor deposition is 400-800°C, for example, 500°C.

[0026] In some embodiments, in step S1, the time of the first vapor deposition is 60-180 min, for example, 120 min.

[0027] In some preferred embodiments, in step S1, the first vapor deposition satisfies: T1≤T2<T3, and P1>P2>P3.

[0028] In some embodiments, in step S2, the second deposition gas further includes a protective gas, and the protective gas preferably includes one or more of nitrogen, helium and argon.

[0029] In some preferred embodiments, in step S2, in the second deposition gas, the volume ratio of the carbon source gas to the protective gas is 1:(0.5-10), for example, 1:4.

[0030] In some preferred embodiments, in step S2, the protective gas and the carbon source gas are introduced in the form of a mixed gas.

[0031] In some embodiments, in step S2, the carbon source gas includes one or more of alkynes (such as acetylene), alkanes, olefins, aromatic compounds (such as one or more of anthracene, naphthalene and lignin) and carbohydrates (such as one or more of glucose, cellulose and hemicellulose).

[0032] In some embodiments, in step S2, the flow rate of the second deposition gas is 0.1-0.5 L·kg - 1 ·min -1 , for example 0.2L·kg -1 ·min -1 The unit of flow rate is relative to the current step per kilogram. The volume of the second deposition gas is introduced into the material below per minute.

[0033] In some embodiments, in step S2, the second vapor deposition time is 30-1200 min, for example, 600 min.

[0034] In some embodiments, in step S2, the temperature of the second vapor deposition is 400-800°C, for example, 550°C.

[0035] In some embodiments, in step S2, before the second vapor deposition, a reducing gas is introduced to reduce the first precursor. The nano-metal oxide is reduced to obtain a nano-metal element, which can further reduce the agglomeration phenomenon and ensure the in-situ growth of carbon nanotubes in a bottom-end growth manner.

[0036] The reduction temperature is preferably 400-800°C, such as 500°C.

[0037] Wherein, the reducing gas preferably includes hydrogen.

[0038] The flow rate of the reducing gas is preferably 0.1-5 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; The unit meaning of the flow rate is the volume of the reducing gas introduced per minute relative to each kilogram of material in the current step.

[0039] The reduction time is preferably 10-600 min, for example 120 min.

[0040] In some embodiments, in step S2, the second vapor deposition further includes washing and drying steps.

[0041] In some embodiments, the washing comprises the steps of washing with hydrochloric acid first and then washing with water. The purpose of the washing is mainly to remove iron-containing substances.

[0042] Wherein, in the hydrochloric acid washing operation, the mass of the hydrochloric acid is preferably 1-100 times, for example 20 times, of the product obtained by the second vapor deposition.

[0043] Wherein, in the hydrochloric acid washing operation, the concentration of the hydrochloric acid is preferably 0.00001-12 mol / L, such as 0.1 mol / L.

[0044] Wherein, in the hydrochloric acid washing operation, the number of times of hydrochloric acid washing is preferably 1-10 times, for example, 2 times.

[0045] The hydrochloric acid washing operation may include soaking the product obtained by the second vapor deposition in hydrochloric acid and then filtering; the soaking time is preferably 1-600 minutes, such as 30 minutes.

[0046] Wherein, in the water washing operation, the mass of the water is preferably 1-20 times, for example 5 times, that of the product obtained by the hydrochloric acid washing.

[0047] Wherein, in the water washing operation, the number of times of water washing is preferably 1-20 times, for example 3 times.

[0048] In some embodiments, the drying is performed using a double cone dryer.

[0049] In some embodiments, the method for preparing the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer, and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet, and a deposition gas outlet provided at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is connected to the first gas inlet of the mixer, and the deposition gas outlet of the mixer is connected to the deposition gas inlet of the reaction furnace;

[0050] In step S1, the gas generator is used to generate metal salt gas, and the metal salt gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer; and then sequentially enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace, and the porous carbon-supported silicon substrate is subjected to a first vapor deposition in the reaction furnace;

[0051] In step S2, the second deposition gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, and the first precursor is subjected to second vapor deposition in the reaction furnace.

[0052] In the present invention, in step S1, the porous carbon-loaded silicon substrate may be conventional in the art, generally comprising porous carbon and silicon, wherein the silicon is distributed in the pores and / or on the surface of the porous carbon; the porous carbon-loaded silicon substrate comprises micropores, mesopores and macropores.

[0053] In the present invention, in step S1, the porous carbon-supported silicon substrate can be prepared by conventional methods in the art.

[0054] In some embodiments, the method for preparing the porous carbon-supported silicon substrate comprises: chemically vapor depositing porous carbon using a silicon source to obtain the porous carbon-supported silicon substrate.

[0055] Wherein, the silicon source for silicon deposition preferably comprises silane (general formula: Si n H 2n+2 ), the silane may include monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8) and tetrasilane (Si4H 10 )

[0056] Preferably, during the silicon deposition process, a silicon source and a carrier gas are introduced simultaneously, wherein the carrier gas is, for example, nitrogen; and the volume ratio of the silicon source to the carrier gas is preferably 1:(2-6), for example, 1:4.

[0057] In the present invention, the porous carbon may be conventional porous carbon in the art, and may be prepared by conventional methods in the art.

[0058] In some embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1200-3000m 2 / g, ② micropores account for 60-100%, ③ mesopores and above account for 0-40%, ④ pore volume is 0.7-1.5cm 3 / g.

[0059] In some specific embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1890 m 2 / g, ② micropores account for 85.3%, ③ mesopores and above account for 14.7%, and ④ pore volume is 1.32cm 3 / g.

[0060] In the present invention, the porous carbon can be prepared by conventional methods in the art. The carbon source of the porous carbon can include one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin.

[0061] In some embodiments, the porous carbon in the porous carbon-supported silicon matrix is ​​prepared using phenolic resin as a carbon source.

[0062] In some specific embodiments, the method for preparing porous carbon comprises the following steps:

[0063] (1) spray drying a slurry containing a phenolic resin to obtain a carbon material precursor;

[0064] (2) carbonizing the carbon material precursor to obtain a porous carbon precursor;

[0065] (3) Activating the porous carbon precursor to obtain porous carbon.

[0066] In step (1), the slurry may further include a curing agent; the curing agent is, for example, hexamethylenetetramine.

[0067] In step (1), the solvent of the slurry is, for example, ethanol.

[0068] In step (2), the carbonization method may be a conventional carbonization method in the art, such as a staged heat treatment; preferably, the carbonization includes the following stages:

[0069] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping the temperature for 60min;

[0070] The second stage: heat up to 652°C at a heating rate of 4°C / min and keep warm for 60 minutes.

[0071] In step (2), the carbonization may be performed under an inert gas, and the inert gas preferably includes one or more of nitrogen, helium and argon.

[0072] In step (3), the activation method can be a conventional activation pore-forming method in the art, such as alkali activation and / or gas activation, preferably gas activation; the gas source of the gas activation is preferably carbon dioxide or water vapor, more preferably carbon dioxide.

[0073] In some embodiments, the method for preparing the porous carbon-supported silicon substrate is carried out in the vapor deposition device; specifically:

[0074] The silicon source gas (or a mixture of the silicon source gas and the carrier gas) is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, and silicon is deposited on the porous carbon in the reaction furnace.

[0075] Preferably, the porous carbon preparation is carried out in the vapor deposition device; specifically:

[0076] The inert gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, and the carbon material precursor is carbonized in the reaction furnace;

[0077] The activation gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, so as to activate the porous carbon precursor in the reaction furnace.

[0078] The present invention also provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.

[0079] In some embodiments, the silicon-carbon material comprises a core-shell structure, wherein the core-shell structure comprises a core, an outer shell and carbon nanotubes; the core comprises porous carbon and silicon particles, and the silicon particles are distributed on the surface and / or in the pores of the porous carbon; the outer shell comprises a carbon layer, and the carbon layer is coated on the surface of the core; wherein the distribution of the carbon nanotubes preferably comprises one or more of the following modes ae:

[0080] a. The carbon nanotubes are distributed on the surface of the porous carbon;

[0081] b. The carbon nanotubes are distributed in the pores of the porous carbon;

[0082] c. The carbon nanotubes extend from the surface of the porous carbon and penetrate the shell;

[0083] d. The carbon nanotubes extend from the pores of the porous carbon and penetrate the shell;

[0084] e. The carbon nanotubes extend from the inside of the shell and penetrate the shell.

[0085] In some embodiments, the silicon carbon material has a silicon content of 45%-55%, such as 49.7%, 49.8%, 49.9%, 50.0%, 50.1%, 50.1%, 50.2% or 50.3%.

[0086] In some embodiments, the silicon-carbon material has a carbon content of 45%-55%, such as 49.7%, 49.8%, 49.9%, 50.0%, 50.1%, 50.1%, 50.2% or 50.3%.

[0087] In some embodiments, the powder conductivity of the silicon carbon material is 10-1100 s / cm, for example, 13.2 s / cm, 25.3 s / cm, 32.2 s / cm, 47.9 s / cm, 54.1 s / cm, 59.2 s / cm, 87.3 s / cm, 106.2 s / cm, 134.2 s / cm, 189.6 s / cm, 309.4 s / cm, 550.9 s / cm, 809.3 s / cm or 1032.1 s / cm.

[0088] In some embodiments, the D50 particle size of the silicon-carbon material is 7.5-9 μm, for example, 7.7 μm, 7.8 μm, 7.9 μm, 8 μm, 8.1 μm, 8.3 μm, 8.5 μm or 8.7 μm.

[0089] In some embodiments, the specific surface area of ​​the silicon-carbon material is 3-16 m 2 / g, for example, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g, 4.3m 2 / g, 4.4m 2 / g, 4.5m 2 / g, 4.7m 2 / g, 5.1m 2 / g, 5.4m 2 / g, 10.3m 2 / g or 15.2m 2 / g.

[0090] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.

[0091] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0092] The reagents and raw materials used in the present invention are commercially available.

[0093] The positive and progressive effects of the present invention are:

[0094] The present invention targets a specific porous carbon-loaded silicon substrate, and deposits and cracks metal salt gas in the mesopores and macropores of the porous carbon-loaded silicon substrate by vapor deposition. Then, a carbon source gas is introduced to grow carbon nanotubes and carbon coating in situ by vapor deposition, thereby comprehensively optimizing the electrical conductivity, compressive strength and other properties of the obtained silicon-carbon material. When used in batteries, the expansion can be effectively alleviated while comprehensively optimizing the first efficiency, rate performance and cycle performance and other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0095] Figure 1 It is a schematic diagram of the structure of the specific device used in the embodiments and comparative examples of the present invention.

[0096] Figure 2 Schematic diagram of the structure of the silicon-carbon material obtained in Examples 1-6 of the present invention.

[0097] Figure 3 Schematic diagram of the structure of the silicon-carbon material obtained in Examples 9-11 of the present invention.

[0098] Figure 4 Schematic diagram of the structure of the silicon-carbon material obtained in Examples 12-14 of the present invention.

[0099] Figure 5 This is a microstructure diagram of the silicon-carbon material obtained in Example 13 of the present invention.

[0100] The reference numerals are as follows:

[0101] 1-gas generator; 2-mixer; 3-reaction furnace;

[0102] 101 - first gas inlet; 102 - second gas inlet; 103 - deposition gas outlet. DETAILED DESCRIPTION

[0103] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0104] Example 1

[0105] S0. Preparation of porous carbon-supported silicon substrate:

[0106] (1) Preparation of carbon material precursor:

[0107] 1 kg of phenolic resin (2153 type, provided by Hubei Hengye Technology Co., Ltd.), 2 kg of ethanol, and 60 g of hexamethylenetetramine (HMT) were mixed and dispersed in a high-speed homogenizer at a speed of 2000 r / min for 60 min. The mixture was spray-dried at 130° C. until the particle diameter was 8 μm.

[0108] (2) Preparation of porous carbon precursor:

[0109] The spray-dried powder was placed in a reactor with a rotation speed of 10 r / min and a nitrogen atmosphere flow rate of 1 L·kg - 1 min -1 , carbonization is carried out: the first stage: the temperature is increased at a heating rate of 4°C / min for 50 minutes, and the temperature is increased to 200°C and kept for 1 hour. The main purpose is to make the phenolic resin cross-linked; the second stage: the temperature is increased at a heating rate of 4°C / min for 113 minutes, and the temperature is increased to 652°C and kept for 1 hour.

[0110] (3) Preparation of porous carbon:

[0111] Activated in CO2 atmosphere, activation time was 9h, flow rate was 2L·kg -1 min -1 The temperature in the furnace was 550°C, and porous carbon was obtained. The specific surface area of ​​the porous carbon was 1890 m 2 / g, micropores account for 85.3%, mesopores and above account for 14.7%, and the pore volume is 1.32cm 3 / g.

[0112] (4) Silicon deposition:

[0113] The atmosphere was switched to monosilane containing carrier gas (20% monosilane and 80% nitrogen by volume) for chemical vapor deposition at 500 °C for 10 h at a flow rate of 15 L kg -1 ·min -1 .

[0114] S1. Preparation of the first precursor:

[0115] Place the metal salt (ferric nitrate) in the gas generator, place the porous carbon-loaded silicon substrate obtained in step S0 in the reactor, then adjust the absolute pressure in the gas generator to 50 kPa, the absolute pressure in the mixer to 40 kPa, and the absolute pressure in the reactor to 30 kPa to ensure that the subsequent metal salt gas enters the mixer from the gas generator at a steady flow rate and then enters the reactor.

[0116] Adjust the temperature in the gas generator and mixer to the sublimation temperature of the metal salt (150°C), and adjust the flow rate of the obtained metal salt gas to 40 mL kg -1 ·min -1 Then, the temperature in the reaction furnace was adjusted to 500° C., and the first vapor deposition was performed for 120 min to obtain the first precursor.

[0117] S2. Preparation of silicon-carbon materials:

[0118] (1) Reduction: With the gas generator turned off, hydrogen was introduced into the mixer and then into the reactor to reduce the first precursor at 500°C at a gas flow rate of 1 L kg -1 ·min -1 , reduction for 120 minutes.

[0119] (2) Second vapor deposition: The atmosphere was switched to acetylene containing a carrier gas (20% acetylene and 80% nitrogen by volume) at a flow rate of 0.2 L kg -1 ·min -1 The temperature is 550°C and the second vapor deposition is carried out for 600 min. During this process, carbon nanotubes are grown in situ while being coated with a carbon layer.

[0120] (3) Washing and drying: Subsequently, the product obtained in step (2) was soaked in 0.1 mol / L hydrochloric acid at a ratio of hydrochloric acid mass: silicon carbon mass = 20:1 for 30 min and washed twice to remove the iron element in the material; the acid-washed product was then washed three times with 5 times the mass of deionized water; the powder rinsed with deionized water was dried using a double cone drying machine, and then sealed and stored to obtain the silicon-carbon material of this embodiment.

[0121] In the above steps, from step (2) of step S0 to the end of step (2) of step S2, the device used is:

[0122] The structure of the vapor deposition device is as follows Figure 1 As shown, the vapor deposition device includes a gas generator 1, a mixer 2 and a reaction furnace 3; the gas generator 1 is provided with a first gas outlet, the mixer 2 includes a first gas inlet 101, a second gas inlet 102 and a deposition gas outlet 103 arranged at different positions, the reaction furnace 3 is provided with a deposition gas inlet, the first gas outlet of the gas generator 1 is connected to the first gas inlet 101 of the mixer 2, and the deposition gas outlet 103 of the mixer 2 is connected to the deposition gas inlet of the reaction furnace 3.

[0123] Accordingly:

[0124] In step (2) of step S0, nitrogen is introduced into the mixer through the second gas inlet, and then enters the reactor through the deposition gas outlet and the deposition gas inlet of the reactor in sequence, with a flow rate of 1 L·kg -1 min -1 , carbonizing the carbon material precursor in a reaction furnace;

[0125] In step (3) of step S0, CO2 is introduced into the mixer through the second gas inlet, and then enters the reactor through the deposition gas outlet and the deposition gas inlet of the reactor in sequence, with a flow rate of 2 L·kg -1 min -1 , activating the porous carbon precursor in a reaction furnace;

[0126] The monosilane containing carrier gas in step (4) of step S0 is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, with a flow rate of 15 L·kg -1 ·min -1 , silicon deposition on porous carbon in a reactor.

[0127] In step S1, ferric nitrate is placed in a gas generator and the temperature is set to the temperature at which the metal salt sublimates (150° C.) to generate metal salt gas. The metal salt gas is sequentially introduced into the mixer through the first gas outlet and the first gas inlet of the mixer, and then sequentially enters the reactor through the deposition gas outlet and the deposition gas inlet of the reactor. The flow rate is 40 mL kg -1 ·min -1 , a first vapor deposition is performed on a porous carbon-supported silicon substrate in a reaction furnace.

[0128] In step (1) of step S2, hydrogen is introduced into the mixer through the second gas inlet, and then successively introduced into Deposition gas out The deposition gas inlet of the reactor enters the reactor at a flow rate of 1 L kg -1 ·min -1 , Reduction is carried out in a reaction furnace.

[0129] In step (2) of step S2, acetylene containing carrier gas is introduced into the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, with a flow rate of 0.2 L·kg -1 ·min -1 , a second vapor deposition is carried out in the reaction furnace to in-situ grow carbon nanotubes while coating them with a carbon layer.

[0130] Embodiment 2-6

[0131] On the basis of Example 1, only the corresponding steps and parameters in step S1 were changed according to Table 1, and the remaining steps and parameters were the same as Example 1, to prepare the silicon-carbon materials of Examples 2-6.

[0132] Example 7

[0133] On the basis of Example 1, the corresponding steps and parameters in step S1 are changed according to Table 1, and the absolute pressure of the first vapor deposition in step S1 is changed to 20 kPa. The remaining steps and parameters are the same as in Example 1, and the silicon-carbon material of Example 7 is obtained.

[0134] Example 8

[0135] On the basis of Example 1, the corresponding steps and parameters in step S1 are changed according to Table 1, and the absolute pressure of the first vapor deposition in step S1 is changed to 50 kPa. The remaining steps and parameters are the same as Example 1, and the silicon-carbon material of Example 8 is obtained.

[0136] Examples 9-14

[0137] On the basis of Example 1, the corresponding steps and parameters in step S1 are changed according to Table 1, and the reduction step in step S2 is not performed. The remaining steps and parameters are the same as in Example 1, and the silicon-carbon materials of Examples 9-14 are obtained.

[0138] Table 1

[0139]

[0140]

[0141] Comparative Example 1

[0142] On the basis of Example 1, the porous carbon-supported silicon substrate prepared in step S0 is directly subjected to steps (2) and (3) in step S2 to obtain the silicon-carbon material of comparative example 1.

[0143] Comparative Example 2

[0144] On the basis of Example 1, step (3) in step S0 is not performed, and the corresponding steps and parameters in step S1 are changed according to Table 1, and the remaining steps and parameters are the same as in Example 1, to obtain the carbon material of Comparative Example 2.

[0145] Effect Example

[0146] The following effect tests were performed on the silicon-carbon materials obtained in Examples 1-14 and Comparative Examples 1-2 respectively:

[0147] 1. Electrochemical performance test

[0148] (1) Button battery preparation

[0149] Preparation of negative electrode slurry and pole piece: The negative electrode formula is designed as CMC:PAA:SBR:SP:CNTs:silicon-carbon material:graphite=0.5:2.5:1:0.1:15:80.9, and the time flow of negative electrode slurry preparation is graphite→CMC→silicon-carbon material→SP→CNTs. After that, it is dispersed for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min. Then, deionized water with a solid content of 40% is injected at one time (only 80% of the amount is added), and it is dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 600r / min. PAA is added and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 500r / min. The remaining 20% ​​of deionized water is injected, and finally SBR is added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution of 300r / min. The coated current collector is 8 μm thick copper foil, coated on both sides, with the coated side facing the negative electrode of the button battery. The thickness of the active material coated on one side is about 40 μm, and the compaction density is 1.8 g / cm 3 (Punch the electrode into a unit circle, test the weight, subtract the weight of the copper foil, and divide it by the thickness to get the compaction density), where the coating speed is 40 cm / s, the baking temperature is 80°C, and the drying time is 400s.

[0150] Preparation of battery electrolyte: The electrolyte composition, by mass percentage, is as follows: the formula is EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS 2.5% and LiODFB 1.5%.

[0151] Half-cell preparation: The positive electrode uses the above single-piece negative electrode plate, the negative electrode uses a lithium sheet, 0.5g of the above electrolyte, assembled into a CR2450 button cell, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.

[0152] (2) Test parameters and steps

[0153] ①First efficiency:

[0154] The button battery was discharged at a constant voltage of 0.1 V / h to 0.000 V, and then charged at 0.1 / h to 0.8 V. The charge and discharge capacity was recorded, and the initial efficiency was obtained by the lithium removal capacity / lithium insertion capacity.

[0155] ② Gram capacity and number of cycles to failure, using Xinwei CT-4008Q-5V6A

[0156] 0.1C 0.8V Gram Capacity:

[0157] The above button battery was discharged at a constant voltage of 0.1 V / h to 0.000 V, and then charged at 0.1 V / h to 0.8 V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 0.1C with the charging capacity recorded. After discharging to 0 V, it was charged to 0.8 V. After the capacity was obtained, the capacity / mass of active matter in the electrode was used to obtain the gram capacity at 0.1C 0.8V.

[0158] 0.5C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively):

[0159] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 0.5C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the gram capacity at 0.1C and 0.8V, and the number of cycles was recorded.

[0160] 1C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively):

[0161] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 1C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the 0.1C, 0.8V capacity, and the number of cycles was recorded.

[0162] ③Rate retention rate

[0163] 25℃ different rate retention rate (%): at 25℃, 1C rate cycle failure number / 0.5C rate cycle failure number.

[0164] 45℃ different rate retention rate (%): at 45℃, 1C rate cycle failure number / 0.5C rate cycle failure number.

[0165] 0.5C hot box cycle retention rate (%): 0.5C 45℃ cycle failure number / 0.5C 25℃ cycle failure number.

[0166] ④ Lithium insertion expansion rate (measured at 25°C and 45°C respectively):

[0167] Lithium insertion expansion rate: (thickness of the electrode after saturated lithium insertion - thickness of the copper foil) / (thickness of the electrode without lithium insertion - thickness of the copper foil)-1.

[0168] 2. Physical and chemical properties test of the obtained silicon-carbon material

[0169] ①Particle size test:

[0170] The D50 particle size was measured using a laser particle size analyzer.

[0171] ②Specific surface area test:

[0172] It is carried out using Mack's ASAP2020.

[0173] ③Carbon content and silicon content test:

[0174] A high frequency carbon and sulfur analyzer (model DK-606) was used.

[0175] ④Iron content test before pickling:

[0176] Take 3 g of the product obtained in step S2(2), dissolve it in 20 mL of aqua regia, and use an inductively coupled plasma spectrometer (ICP, model Agilent 5800, provided by Agilent) to test the iron ion content of the filtered eluate. The mass percentage of iron element in the product obtained in step S2(2) can be calculated, which is the iron element content C0 before pickling.

[0177] ⑤ Iron content test after pickling:

[0178] Take 3 g of the final silicon-carbon material, use 20 mL of aqua regia to dissolve it, use an inductively coupled plasma spectrometer (ICP, model Agilent 5800, provided by Agilent) to test the iron ion content of the filtered eluate, and calculate the mass percentage of iron element in the silicon-carbon material, which is the iron element content after acid washing.

[0179] ⑥Test of iron content before pickling:

[0180] Take 3 g of the product obtained in step S2(2) and demagnetize it using a Guoming (GDG220) demagnetizer. Record the mass difference of the product before and after demagnetization. The mass difference is the mass of the magnetic substance (mainly iron) in the product, which is further calculated according to the following formula:

[0181] Iron content before pickling C1 (%) = (m0-m1) / m0×100;

[0182] Wherein, m0 is the mass of the product before demagnetization, and m1 is the mass of the product after demagnetization.

[0183] ⑦ Test of ferric oxide content before pickling:

[0184] The determination is carried out by estimation, that is, the total mass of the iron element before pickling is approximately the sum of the mass of the iron element and the mass of the iron in the ferric oxide; specifically, the results obtained in the above test steps ④ and ⑥ are calculated according to the following formula to obtain the content of ferric oxide:

[0185] Iron oxide content before pickling (%) = (C0-C1) × M1 / M2;

[0186] Wherein, C0 is the content of iron element before pickling, C1 is the content of single iron before pickling, M1 is the molar mass of ferric oxide, and M2 is the molar mass of iron.

[0187] ⑧Raman spectroscopy test (Raman):

[0188] There are two characteristic peaks in the Raman spectrum curve of silicon-carbon materials, with the peak values ​​located at 1310-1360cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peaks between are stones Black peak (G peak). The integrated area of ​​D peak and G peak The ratio (ID / IG) can characterize the disorder of silicon-carbon materials The smaller the ID / IG, the lower the disorder degree, the higher the graphitization degree, and the stronger the buffering effect of the obtained material on the expansion of silicon-intercalated lithium.

[0189] ⑨Powder conductivity test:

[0190] The test is carried out using a powder conductivity meter (model FT-8100) based on the four-probe test principle and the test standard is GB / T1552-1995. A known amount of silicon-carbon material solid powder is used to compress the volume to a set pressure value or pressure under hydraulic power, and the conductivity of the silicon-carbon material solid powder is measured online.

[0191] The results are shown in Tables 2 to 4 respectively.

[0192] Table 2

[0193]

[0194]

[0195] Table 3

[0196]

[0197] Table 4

[0198]

[0199]

[0200] Generally speaking, after the growth of carbon nanotubes, silicon-carbon materials tend to improve their conductivity, reduce ID / IG, increase specific surface area, and enhance strength. While enhancing their strength, carbon nanotubes also inhibit the expansion of micropores during lithium insertion to a certain extent, regulate the filling degree of silicon in the micropores, and help improve the anti-expansion performance. After being used in batteries, carbon nanotubes have good elasticity and can effectively inhibit the thickening of the sei film caused by the expansion of silicon-carbon materials, and the stable sei film can greatly improve the cycle performance of the resulting battery; in addition, the growth of carbon nanotubes actually indirectly increases the thickness of the carbon layer, which is conducive to suppressing the problem of thermal runaway and improving the thermal cycle retention rate; and because carbon nanotubes grow anisotropically, they have overall directionality during growth, and grow outward along the radius, allowing lithium ions to directly enter the center of the silicon-carbon material. Even in the extremely high impedance test system of button batteries, its rate performance is still excellent.

[0201] It can be seen from the results of Tables 2 to 4 that after the metal salt gas and the carbon source gas are introduced, the silicon-carbon materials obtained in Examples 1-14 have lower ID / IG, higher electrical conductivity and larger specific surface area than the comparative example 1 in which no metal salt is introduced. When used in batteries, they have at least a higher first efficiency, and may even have better anti-expansion performance, higher cycle performance, higher rate performance and higher thermal cycle performance at the same time; this indicates that when the carbon source gas is introduced in Examples 1-14 of the present invention, carbon nanotubes are grown in situ while the carbon is coated.

[0202] Specifically, in Examples 1-8 of the present invention, metal salt (such as iron salt) gas is deposited in the micropores, mesopores, macropores and surface of the porous carbon-supported silicon substrate, and is cracked into corresponding metal oxides (such as ferric oxide), which are reduced to elemental metal particles by hydrogen. Subsequently, when a carbon source gas (such as acetylene) is introduced, carbon nanotubes are in situ grown at the metal particles in a bottom-end growth manner, and carbon coating of the entire material is simultaneously performed. The structural schematic diagram of the resulting silicon-carbon material is shown in FIG. Figure 2 As shown, as the amount of metal salt gas increases, the growth of carbon nanotubes becomes better, and when the amount reaches that of Example 4, the effect is optimal.

[0203] In Examples 9-14, when metal salt gas is introduced without hydrogen reduction, carbon nanotubes are grown in situ at the metal oxide particles in a top growth manner after acetylene is introduced. As the amount of metal salt gas increases, the number of carbon nanotubes increases. When the amount is too much, the carbon layer may break (such as in Example 14). Although some of the effects are not as good as those in Comparative Example 1, they still have higher conductivity and first effect. Correspondingly, the structural schematic diagrams of the obtained silicon-carbon materials are as follows: Figure 3 (Examples 9-11) and Figure 4 As shown in (Examples 12-14), the microstructure after the growth of carbon nanotubes is as follows Figure 5 As shown in Example 13, in contrast, the silicon-carbon materials of Examples 1-8 do not have the carbon layer cracking, and accordingly, the overall performance is also better.

[0204] In comparative example 2, when unactivated porous carbon (equivalent to hard carbon) is used for silicon deposition, the amount of silicon deposition is significantly reduced (close to carbon material as a whole), which ultimately leads to a significant reduction in the capacity of the resulting silicon-carbon material when used in batteries.

Claims

1. A method for preparing a silicon-carbon material, characterized in that: The preparation method of the silicon-carbon material comprises the following steps: S1, performing a first vapor deposition on a porous carbon-supported silicon substrate to obtain a first precursor; Wherein, the first deposition gas used in the first vapor deposition comprises a metal salt gas; S2, performing a second vapor deposition on the first precursor to obtain the silicon-carbon material; Wherein, the second deposition gas used in the second vapor deposition comprises a carbon source gas.

2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the metal salt gas includes one or more of metal nitrate gas, metal hydrochloride gas, metal sulfate gas, metal acetate gas and metal citrate gas, preferably metal nitrate gas; And / or, in step S1, the metal salt gas includes one or more of iron salt gas, nickel salt gas, molybdenum salt gas and cobalt salt gas; Preferably, in step S1, the metal salt gas includes iron salt gas, more preferably includes iron nitrate gas.

3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the metal salt gas is obtained by heating and sublimating the metal salt; Preferably, the absolute pressure P1 of the heating treatment is 30-60 kPa, for example 50 kPa; Preferably, the temperature T1 of the heating treatment is 80-550°C, for example 150°C; And / or, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at an absolute pressure P2 of 25-55 kPa, for example, 40 kPa; And / or, in step S1, before the first deposition gas is introduced, the environment in which the first deposition gas is located is maintained at a temperature T2 of 80-550° C., for example, 150° C.; And / or, in step S1, the flow rate of the first deposition gas is 3-80 mL·kg -1 ·min -1 , preferably 10-60mL·kg -1 ·min -1 , more preferably 40 mL·kg -1 ·min -1 ; and / or, in step S1, the absolute pressure P3 of the first vapor deposition is 20-50 kPa, for example, 30 kPa; and / or, in step S1, the temperature T3 of the first vapor deposition is 400-800° C., for example, 500° C.; And / or, in step S1, the first vapor deposition time is 60-180 min, for example, 120 min; Preferably, in step S1, the first vapor deposition satisfies: T1≤T2<T3, and P1>P2>P3.

4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the second deposition gas also includes a protective gas; Preferably, the protective gas includes one or more of nitrogen, helium and argon; Preferably, the volume ratio of the carbon source gas to the protective gas is 1:(0.5-10), for example 1:4; Preferably, the protective gas and the carbon source gas are introduced in the form of a mixed gas; and / or, in step S2, the carbon source gas comprises one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; And / or, in step S2, the flow rate of the second deposition gas is 0.1-0.5 L·kg -1 ·min -1 , for example 0.2L·kg -1 ·min -1 ; And / or, in step S2, the second vapor deposition time is 30-1200 min, for example, 600 min; And / or, in step S2, the temperature of the second vapor deposition is 400-800°C, for example, 550°C.

5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, before the second vapor deposition, a reducing gas is introduced to reduce the first precursor; Wherein, the reduction temperature is preferably 400-800°C, for example 500°C; Wherein, the reducing gas preferably comprises hydrogen; The flow rate of the reducing gas is preferably 0.1-5 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; The reduction time is preferably 10-600 min, for example 120 min.

6. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the second vapor deposition further includes washing and drying steps; The washing step preferably includes washing with hydrochloric acid first and then washing with deionized water.

7. The method for preparing the silicon-carbon material according to claim 1, characterized in that: The preparation method of the silicon-carbon material is carried out in a vapor deposition device, which includes a gas generator, a mixer and a reaction furnace; the gas generator is provided with a first gas outlet, the mixer includes a first gas inlet, a second gas inlet and a deposition gas outlet arranged at different positions, the reaction furnace is provided with a deposition gas inlet, the first gas outlet of the gas generator is communicated with the first gas inlet of the mixer, and the deposition gas outlet of the mixer is communicated with the deposition gas inlet of the reaction furnace; In step S1, the gas generator is used to generate metal salt gas, and the metal salt gas enters the mixer through the first gas outlet and the first gas inlet of the mixer in sequence; and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, and the porous carbon-loaded silicon substrate is subjected to a first vapor deposition in the reaction furnace; In step S2, the second deposition gas enters the mixer through the second gas inlet, and then enters the reaction furnace through the deposition gas outlet and the deposition gas inlet of the reaction furnace in sequence, and performs second vapor deposition on the first precursor in the reaction furnace.

8. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 7.

9. The silicon-carbon material according to claim 8, characterized in that: The silicon-carbon material comprises a core-shell structure, wherein the core-shell structure comprises a core, an outer shell and carbon nanotubes; the core comprises porous carbon and silicon particles, wherein the silicon particles are distributed on the surface and / or in the pores of the porous carbon; the outer shell comprises a carbon layer, wherein the carbon layer is coated on the surface of the core; The distribution of the carbon nanotubes preferably includes one or more of the following methods ae: a. The carbon nanotubes are distributed on the surface of the porous carbon; b. The carbon nanotubes are distributed in the pores of the porous carbon; c. The carbon nanotubes extend from the surface of the porous carbon and penetrate the shell; d. The carbon nanotubes extend from the pores of the porous carbon and penetrate the shell; e. The carbon nanotubes extend from the inside of the shell and penetrate the shell; and / or, the silicon carbon material has a silicon content of 45%-55%, such as 49.7%, 49.8%, 49.9%, 50.0%, 50.1%, 50.1%, 50.2% or 50.3%; and / or, the carbon content of the silicon-carbon material is 45%-55%, such as 49.7%, 49.8%, 49.9%, 50.0%, 50.1%, 50.1%, 50.2% or 50.3%; and / or, the powder conductivity of the silicon-carbon material is 10-1100 s / cm, for example, 13.2 s / cm, 25.3 s / cm, 32.2 s / cm, 47.9 s / cm, 54.1 s / cm, 59.2 s / cm, 87.3 s / cm, 106.2 s / cm, 134.2 s / cm, 189.6 s / cm, 309.4 s / cm, 550.9 s / cm, 809.3 s / cm or 1032.1 s / cm; And / or, the D50 particle size of the silicon-carbon material is 7.5-9 μm, for example, 7.7 μm, 7.8 μm, 7.9 μm, 8 μm, 8.1 μm, 8.3 μm, 8.5 μm or 8.7 μm; And / or, the specific surface area of ​​the silicon-carbon material is 3-16m 2 / g, for example, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4m 2 / g, 4.1m 2 / g, 4.3m 2 / g, 4.4m 2 / g, 4.5m 2 / g, 4.7m 2 / g, 5.1m 2 / g, 5.4m 2 / g, 10.3m 2 / g or 15.2m 2 / g.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the silicon-carbon material as claimed in claim 8 or 9.